Natural and Experimental Constraints on a Flow Law for Dislocation‐Dominated Creep in Wet Quartz. Issue 5 (15th May 2021) - Lusk, Alexander D. J.; Platt, John P.; Platt, Jason A.
Abstract: We present a flow law for dislocation‐dominated creep in wet quartz derived from compiled experimental and field‐based rheological data. By integrating the field‐based data, including independently calculated strain rates, deformation temperatures, pressures, and differential stresses, we add constraints for dislocation‐dominated creep at conditions unattainable in quartz deformation experiments. A Markov Chain Monte Carlo (MCMC) statistical analysis computes internally consistent parameters for the generalized flow law: ε ˙ = Aσ n f H 2 O r e −( Q + V P)/ RT . From this initial analysis, we identify different effective stress exponents for quartz deformed at confining pressures above and below ∼700 MPa. To minimize the possible effect of confining pressure, compiled data are separated into "low‐pressure" (<560 MPa) and "high‐pressure" (700–1, 600 MPa) groups and reanalyzed using the MCMC approach. The "low‐pressure" data set, which is most applicable at midcrustal to lower‐crustal confining pressures, yields the following parameters: log( A ) = −9.30 ± 0.66 MPa − n − r s −1 ; n = 3.5 ± 0.2; r = 0.49 ± 0.13; Q = 118 ± 5 kJ mol −1 ; and V = 2.59 ± 2.45 cm 3 mol −1 . The "high‐pressure" data set produces a different set of parameters: log( A ) = −7.90 ± 0.34 MPa − n − r s −1 ; n = 2.0 ± 0.1; r = 0.49 ± 0.13; Q = 77 ± 8 kJ mol −1 ; and V = 2.59 ± 2.45 cm 3 mol −1 . Predicted quartz rheology is compared to other flow laws for dislocation creep; the calibrations presented in this study predict faster strain rates under geological conditions by more than 1 order of magnitude. The change in n at high confining pressure may result from an increase in the activity of grain size sensitive creep. Plain Language Summary: At conditions present in the middle and lower crust, rocks generally deform by ductile processes, instead of brittle fracture which is dominant closer to the Earth's surface. As a volumetrically dominant mineral in many crustal rocks, quartz is commonly thought to control the overall strength of the crust. Much of our understanding of how quartz behaves comes from deformation experiments; but to produce the same type of deformation we observe in middle‐ or lower‐crustal rocks, experiments must be performed at conditions different from what natural rocks experience. The difference poses a potential issue in extrapolating experimental results to natural conditions. Here, we integrate mechanical data from deformation experiments and naturally deformed rocks to arrive at a quantitative relationship that relates material properties and deformation conditions to the rate at which quartz deforms. Because we add constraints at deformation conditions not attainable in experiments, we likely produce a more accurate representation of ductile quartz behavior. Our results indicate that quartz‐rich rocks in the middle and lower crust deform at least an order of magnitude faster than previous predictions, which has important implications for crustal strength, geodynamic modeling, and potentially for the loading of seismically active faults. Key Points: We use Bayesian statistical analysis on compiled rock deformation data to produce a flow law for dislocation creep in wet quartz This analysis indicates a low sensitivity to water fugacity, while other parameters are broadly consistent with existing values Under geological conditions, wet quartz aggregates deform faster than is predicted by existing flow laws